Small RNA-based antimicrobial immunity - Guo, Zhongxin; Li, Yang; Ding, Shou-Wei (Nature reviews. Immunology, 2019)
Protection against microbial infection in eukaryotes is provided by diverse cellular and molecular mechanisms. Here, we present a comparative view of the antiviral activity of virus-derived small interfering RNAs in fungi, plants, invertebrates and mammals, detailing the mechanisms for their production, amplification and activity. We also highlight the recent discovery of viral PIWI-interacting RNAs in animals and a new role for mobile host and pathogen small RNAs in plant defence against eukaryotic pathogens. In turn, viruses that infect plants, insects and mammals, as well as eukaryotic pathogens of plants, have evolved specific virulence proteins that suppress RNA interference (RNAi). Together, these advances suggest that an antimicrobial function of the RNAi pathway is conserved across eukaryotic kingdoms.